2004
DOI: 10.1073/pnas.0405905101
|View full text |Cite
|
Sign up to set email alerts
|

Defective lysosomal exocytosis and plasma membrane repair in Chediak–Higashi/beige cells

Abstract: Plasma membrane resealing is a Ca 2؉ -dependent process that involves the exocytosis of intracellular vesicles next to the wound site. Recent studies revealed that conventional lysosomes behave as Ca 2؉ -regulated secretory compartments and play a central role in membrane resealing. These findings raised the possibility that the complex pathology of lysosomal diseases might also include defects in plasma membrane repair. Here, we investigated the capacity for lysosomal exocytosis and membrane resealing of fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
3
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 32 publications
6
95
3
2
Order By: Relevance
“…However, MHCII molecules may recycle through an early endosomal compartment dependent on the homologous fusion of early endosomes controlled by Rab5 so that the lack of Rab5 activity may lead to default delivery to late endosomes and then by normal endolysosomal Rab7-dependent maturation mechanisms to the lysosomes. Because Bg cells show defective trafficking to the late endosomal compartments and increased ability of these lysosomes to fuse with the plasma membrane (42,43), the loss of Nef-mediated MHCII down-regulation in Bg cells can perhaps be explained either by enhanced recycling back to the cell surface from early endosomes and/or by fusion of Bg lysosomes with the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, MHCII molecules may recycle through an early endosomal compartment dependent on the homologous fusion of early endosomes controlled by Rab5 so that the lack of Rab5 activity may lead to default delivery to late endosomes and then by normal endolysosomal Rab7-dependent maturation mechanisms to the lysosomes. Because Bg cells show defective trafficking to the late endosomal compartments and increased ability of these lysosomes to fuse with the plasma membrane (42,43), the loss of Nef-mediated MHCII down-regulation in Bg cells can perhaps be explained either by enhanced recycling back to the cell surface from early endosomes and/or by fusion of Bg lysosomes with the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of dominant-negative constructs or the genetic ablation of Syt VII results in impaired lysosomal exocytosis (6,10,11), and in marked alterations in the lysosomal secretion pattern (12). Previous studies using cells defective in lysosomal-regulatory proteins, such as the LYST protein that carries the mutation leading to enlarged lysosomes in ChediakHigashi/beige syndrome (13), showed that similar secretory defects are found in fibroblast conventional lysosomes (14) and in CTL lytic granules (15). Given that exocytosis of conventional lysosomes is also impaired in fibroblasts from Syt VII-deficient mice (10,11), we investigated whether a similar functional defect was present in CTLs from these animals.…”
Section: A Ctivated Cd8mentioning
confidence: 97%
“…In specialized cells, such as cytotoxic T cells from CHS patients, lysosomes formed during differentiation are enlarged and are not secreted upon stimulation, although their content is apparently normal (Baetz et al, 1995). Non-specialized CHS cells also present enlarged lysosomes, which fail to fuse efficiently with the cell surface in response to membrane lesions (Huynh et al, 2004). The gene mutated in patients with CHS encodes a protein named lysosomal trafficking regulator or LYST (previously known as CHS1 in human and beige in mouse) (Barbosa et al, 1996;Nagle et al, 1996;Perou et al, 1996).…”
Section: Introductionmentioning
confidence: 99%